FEMINISME MARXIS DALAM NOVEL TEMPURUNG KARYA OKA RUSMINI - Gaudensia Ratna Sari; Agung Pramujiono (Buana Bastra, 2019)
This study aims to describe Marxist feminism in Tempurung novels by Oka Rusmini. Marxist feminism is a problem related to social classes in the family and society. Marxist feminism is important to study, because in family life and in people's lives there are so many problems related to social classes especially those that occur in women. This research is a qualitative research with descriptive method. the data from this study are in the form of sentences that contain quotations containing Marxist feminism. The data source of this research is the Tempurung novel by Oka Rusmini. The technique used in collecting data is documentation techniques, because it collects data from written information in the form of Tempurung novels by Oka Rusmini. The results of this study of Marxist feminism show that in family life and in society there are still differences in social classes, especially in women. In this case women experience various kinds of problems, such as: women's position based on socio-economic and women's position based on social class in society. The position of women based on socio-economic conditions includes economic exploitation of employment and economic exploitation of marriage. Whereas the position of women based on social class in society includes class differences in family and class differences in society.